INTEGRACIJA NEMŠKE LITERARNE PRODUKCIJE NA SLOVENSKEM V OKVIR SLOVENSKE LITERARNE VEDE Z VIDIKA SISTEMSKEGA PRISTOPA (Philological Studies, 2019)
The article suggests theoretical criteria for the inclusion of Slovenia-based German literary production (particularly that of the 19th century) in the framework of Slovenian literary studies. The fundamental research of this production carried out within the field of Slovenian studies as well as that done by Slovenian Germanists is listed in the first part of the article. The integration of this literature into the Slovenian studies is justified sociologically as well as by its internal aspects. The argument is corroborated by the Schmidt conception of culture as a collective national programme. In this way, Slovenian and German literary production on Slovenian territory become parts of the same research focus.